PENGARUH MINAT BELAJAR SISWA TENTANG HUKUM NEWTON III DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Marsesi; Nurul Apsari (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2026)
This study aims to determine the effect of students' interest in learning about Newton's Third Law with the Problem Based Learning Learning Model. The problem in this study is to find out how students' interest in learning after applying the Problem Based Learning learning model. This type of research is qualitative research with a descriptive qualitative type. The population in this study were grade X students of Bhakti Setia High School with a sample of 21 students. Data collection techniques used non-tests. The research instruments used observation sheets, questionnaires and interview sheets. Data analysis techniques used were data reduction, data presentation, drawing conclusions. Checking the validity of the data in this study was carried out using technical triangulation. Indicators of interest in the attention aspect were the category of quite interested by 16%, the category of interested by 27.17% and the category of very interested by 56.73%. Interest indicators for the feeling of pleasure aspect were: moderately interested (7.84%), interested (33.26%), and very interested (58.88%). Interest indicators for the interest aspect were: not interested (3.33%), moderately interested (12.50%), interested (12.76%), and very interested (71.39%). Interest indicators for the participation aspect were: not interested (1.6%), moderately interested (0.01%), interested (23.93%), and very interested (71.22%). All interest indicators were dominant in the very interested category. The conclusion of this study is that the application of the Problem-based learning model has a positive influence on students' learning interest.